2011
DOI: 10.1345/aph.1p477
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Understanding of Prescription Drug Information: An Illustration Using an Antidepressant Medication

Abstract: Information provided with at least some prescription drugs is not adequately understood by less-educated consumers and does not effectively communicate critical safety messages or directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 10 publications
1
45
0
7
Order By: Relevance
“…Provider perspectives on how people understand information has focused on ensuring that patients receive disease and treatment information at the correct reading level and in the correct language (Shiffman, Gerlach, Sembower, & Rohay, 2011); on the importance of taking HIV medication (Millard, Elliott, & Girdler, 2013); and on how to address symptoms and manage side effects (Okonsky et al, 2014). It does not always, however, prioritize building and maintaining long-term relationships between patients and providers, as our data suggest is so important.…”
Section: Discussionmentioning
confidence: 99%
“…Provider perspectives on how people understand information has focused on ensuring that patients receive disease and treatment information at the correct reading level and in the correct language (Shiffman, Gerlach, Sembower, & Rohay, 2011); on the importance of taking HIV medication (Millard, Elliott, & Girdler, 2013); and on how to address symptoms and manage side effects (Okonsky et al, 2014). It does not always, however, prioritize building and maintaining long-term relationships between patients and providers, as our data suggest is so important.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates previous findings of associations between lower health literacy and lower health care knowledge. 4,13,18 In asthma, health literacy has been shown to be associated with improved disease management and outcomes, including increased disease knowledge, proper inhaler use, improved asthma control, improved quality of life, and fewer emergency department visits, [19][20][21] and it has been suggested that in COPD, adherence to therapy and health outcomes are both related to health literacy. 22 Patient-directed materials including MGs have welldocumented shortcomings, which may partially explain why these materials are inconsistently read by patients.…”
Section: Disantostefano Et Al 579mentioning
confidence: 99%
“…Neste contexto os doentes têm oportunidade de esclarecer as suas dúvi-das e de receber informações consideradas determinantes para a utilização racional e segura dos medicamentos. [29][30][31] Complementarmente, a investigação sobre a adequabilidade da apresentação e da extensão dos FIs, assim como a avaliação do impacto da utilização de FIs mistos nos resultados em saúde, deveria incluir testes de legibilidade específicos para avaliar as variações na resposta entre os doentes ou potenciais utilizadores dos medicamentos dos diferentes países da União Europeia, já que as populações destes países apresentam diferentes níveis educacionais. 26 Embora este não tenha sido o foco principal da presente investigação, verificou-se que alguns FIs estavam indisponíveis na base Infomed, o que eventualmente poderá comprometer o acesso imediato à informação por parte dos utilizadores da base (doentes ou profissionais de saúde), ainda que os profissionais de saúde supostamente consultem preferencialmente o resumo das características do medicamento, que também se encontra publicado nesta base.…”
Section: Considerações Finaisunclassified